Fetal germ cell differentiation and the impact of the somatic cells - Cowan, Gillian (The University of Edinburgh, 2009)
Specification of a germ cell lineage and appropriate maturation are essential for the transfer of genetic information from one generation to the next. Germ cells form from pluripotent precursor cells that migrate into the gonadal ridge and undergo commitment to either the female or male lineage. In the fetal ovary, germ cells enter meiotic prophase I, then arrest at the diplotene stage; in the testis germ cells do not begin meiosis until puberty. Abnormal differentiation of germ cells can result in malignant transformation. Somatic cells play a key role in modulating the developmental fate of the germ cells. Research into germ cell development during fetal life has almost exclusively focused on studies in rodents, but we, and others, have reported several fundamental differences in the expression of germ cell specific markers in the human compared with the mouse. The studies described in this thesis have investigated germ cell-specific gene expression and the possible impact of the somatic cells during development. This was achieved by studying human fetal gonads obtained during the 1st and 2nd trimesters of pregnancy and through the use of both wild-type and mutant mouse ES cell lines. Studies on germ cells in the human fetal testis have extended the findings of others, and confirmed that germ cell populations at different stages of maturation co-exist in the human fetal testis, a situation that is in contrast to that in rodents. For example expression of M2A and AP2γ was restricted to the OCT4-positive gonocyte population, while VASA and NANOS1 were localised exclusively to the to the OCT4-negative prespermatogonia. DAZL was expressed in both populations. Analysis also revealed that both the gonocyte and prespermatogonial populations proliferate throughout the 2nd trimester. Recent studies have implicated retinoic acid (RA) in the control of meiotic entry in germ cells of the fetal mouse ovary. In this study we demonstrated for the first time that two genes implicated in the action of RA in mouse gonad, STRA8 and NANOS2, are also expressed in a similar sexspecific- manner in the human fetal gonads, and that the RA receptors are present in both somatic and germ cells suggesting that RA may regulate germ cell function in the human as well as the mouse. However, whilst the mesonephros appears to be the primary site of RA synthesis in the mouse our initial studies indicate that in the human the gonad itself may be a more likely site of RA biosynthesis. In the fetal mouse testis, RA is degraded by the enzyme Cyp26b1 present in the somatic cells and germ cells do not enter meiosis, our novel findings suggest that CYP26B1 is more abundant in the human fetal ovary than the testis, suggesting that meiotic entry may be controlled by an alternative signalling pathway in the human. One of the methods that can aid our understanding of somatic cell gene expression in the gonad is in vitro culture. To date, there have been no published reports of the successful in vitro culture of somatic cells from the human fetal testis. In the current study, populations of human somatic cells were dissociated and maintained in vitro and characterised. Analysis demonstrated that cells expressing mRNAs characteristic of Sertoli cells, Leydig cells and peritubular myoid (PTM) cells were present initially, but long-term culture resulted in downregulation in expression of mRNAs specific for Sertoli cells and Leydig cells, suggesting that these cells either failed to survive or underwent alterations to their phenotype. In contrast PTM/fibroblast cells proliferated in vitro and initially maintained androgen receptor expression. These cultures therefore hold promise for studies into the signalling or cell-cell interactions in testicular somatic cells especially those relevant to the PTM population. Several studies have claimed differentiation of putative germ cells from ES cells. In the current study, analysis of mouse ES cell lines has expanded on results showing that ES cells and early germ cells express a number of genes in common. Kit signalling was shown to be important for ES cell survival as they differentiate although expression of Kit was heterogeneous. We also demonstrated that ES cells that did not express Kit displayed a decreased expression of the early germ cell genes Blimp1, Fragilis and Stella, implicating Kit signalling in the control of germ cell-associated gene expression in ES cells. This may be important to future studies optimising germ cell derivation from ES cells. In conclusion, this study has demonstrated important differences in protein expression patterns in germ cells of the human fetal testis compared to the mouse, and has raised questions about whether the proposed mechanism controlling meiotic entry of germ cells in the mouse can be applied to the human. The establishment of a system for culturing human fetal gonadal somatic cells may lead to further understanding of gene expression and development in the human fetal testis, and data suggest that the Kit/Kitl signalling system may influence germ cell gene expression in mouse ES cells.
Keywords: germ cells; sertoli cells; ES cells; meiosis